Implementation of Mechanisms for Checking the Election Results in the Digital Election System (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article comprehensively analyzes the main trends of the implementation of election result in the digital election system, the benefits to the states in performing their functions, the implementation problems and the impact on efficiency. This mechanism increases the productivity of the organizational work in the elections, the quality of service and provides an opportunity to reduce costs. However, it is no secret that financial barriers, lack of technical knowledge and problems related to data security may prevent it. Therefore, theoretical and practical recommendations were developed for the effective implementation of the mechanisms of verification of election results through the digital election system in the Republic of Uzbekistan.